2003
DOI: 10.1097/00126334-200305010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Is a Powerful Predictor of Survival Among HIV-1–Infected Women

Abstract: Serum albumin is a strong independent predictor of mortality in HIV-1-infected women after adjustment for known disease markers and may be useful for clinical monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 29 publications
6
51
1
Order By: Relevance
“…The difference between the groups was statistically significant. Although no correlation was observed between albumin after 6 months and baseline CD4 count in our study, other investigators have observed a positive correlation between albumin and CD4 in HIV patients initiating ARV [32,34,36,37]. The fact that these patients were initiating ARV, indirectly indicate that they were at an advanced stage of the infection (i.e., CD4 counts below 350 cells/µl).…”
Section: Discussioncontrasting
confidence: 75%
“…The difference between the groups was statistically significant. Although no correlation was observed between albumin after 6 months and baseline CD4 count in our study, other investigators have observed a positive correlation between albumin and CD4 in HIV patients initiating ARV [32,34,36,37]. The fact that these patients were initiating ARV, indirectly indicate that they were at an advanced stage of the infection (i.e., CD4 counts below 350 cells/µl).…”
Section: Discussioncontrasting
confidence: 75%
“…The same group went on to study serial albumin measurements prior to HAART initiation and concluded that albumin was a strong independent predictor of mortality, particularly in the short term [25]. The association between albumin and progression to AIDS was not investigated in this study as the number of AIDS events was small.…”
Section: Discussionmentioning
confidence: 98%
“…Different hypotheses have been proposed to explain the low levels of albumin seen in HIV infection [15]. Some studies have demonstrated that HIV co-infection with HCV accelerates the progression of liver disease while other studies have found albumin to be a significant predictor of HIV disease progression even among those not infected with HCV [16]. It is also possible that low that low albumin levels may reflect the effects of anorexia, poor nutritional status or chronic inflammation (albumin is a negative acute phase reactive protein whose levels can possibly be depressed by elevated levels of TNF and IL-1 during chronic inflammation) [15].…”
Section: Discussionmentioning
confidence: 99%